Pleiotropic effects of metformin on the chemotherapy response of HPV-positive cancer cells - Avenhaus, Alicia; Kuhn, Bianca; Velimirović, Milica; Strobel, Tobias; Bulkescher, Julia; Lohrey, Claudia; Krijgsveld, Jeroen; Hoppe-Seyler, Felix; Hoppe-Seyler, Karin (Journal of medical virology, 2025)
Improved treatment strategies for HPV-positive cancers are urgently required. The viral E6/E7 oncoproteins are essential for the proliferation of HPV-positive cancer cells and considered attractive therapeutic targets. Metformin is proposed to be repurposed for cancer therapy, but this is under controversial debate. We previously demonstrated that E6/E7 expression and the proliferation of HPV-positive cancer cells are repressed by Metformin. Here, we explore the effects of Metformin on the phenotype of HPV-positive cancer cells in detail, either applied as monotreatment or in combination with chemotherapeutic agents. We provide evidence that the downregulation of E6/E7 is not the primary mechanism underlying Metformin's growth-inhibitory effect in HPV-positive cancer cells. Specifically, compared to targeted E6/E7 repression by RNA interference (RNAi), Metformin treatment differently altered the expression of growth regulatory proteins, exerted different effects on the cell cycle, and was able to suppress growth even in the presence of E6/E7. Furthermore, we found that cancer cells pre-treated with Metformin become resistant to senescence induction by the pro-senescent chemotherapeutic agent Etoposide, likely as a secondary effect of Metformin-induced growth inhibition. Finally, depending on experimental conditions, we uncover divergent, even opposing, effects on the proliferation of HPV-positive cancer cells when Metformin is combined with Cisplatin, with p53 playing a key role in these processes. Collectively, our results show that Metformin exerts complex effects on the phenotype of HPV-positive cancer cells, which are critically influenced by experimental conditions. Our findings may also explain the discrepant results in the literature, reporting agonistic or antagonistic effects upon combining Metformin with Cisplatin.